Farmers ' Awareness and Understanding of Climate Change and Variability in Central Semi-arid Tanzania - Elia, Emmanuel (University of Dar es Salaam Library Journal, 2018)
This study investigated the farmers ' awareness and knowledge of climate change and variability farmers in Tanzania. The study applied a qualitative approach in data collection and analysis. It used interviews and focus group discussions as data collection methods. The study population comprised of farmers. The qualitative data was subjected to content analysis. Key findings show that farmers are aware of climate change and variability and have coping and adaptation knowledge. Despite being aware and practicing adaptation farmers still do not have a clear understanding of climate change and variability. The factors, which affect farmers ' awareness and understanding, are the types of media used in communication, communication gaps, unreliable and untimely information, low income and budget constraints. As such, the study recommends intensive awareness and sensitisation, timely access to information and frequent contacts between researchers, extension officers and farmers.